Organisational resilience in a higher education institution: Maintaining academic continuity, academic rigour and student experience in the face of major disruption (Covid-19 pandemic) (Journal of Applied Learning and Teaching, 2024)
This paper aims to understand how an institution responds to a major disruption such as the Covid-19 pandemic by focusing in detail on one university in England. The study collected data from a range of levels, including survey data from students and staff as well as recruitment data, degree outcomes and financial impact to explore how academic continuity, academic rigour and student experience can be maintained.Using a systems-based approach and drawing on an organisational resilience framework, findings demonstrated that the case study university had made a positive adjustment to the pandemic. It managed to maintain academic continuity, rigour, and the student experience. What was less clear were the longer-term impacts and the extent of that resilience as defined in the organisational resilience literature which focuses on adversity as an opportunity to learn and land in an overall better place after adversity rather than return to a ‘business as before’ place.  This is applicable to other universities that made similar adjustments in response to the pandemic. A better understanding of organisational resilience in higher education institutions is important in order to enable them to plan for other such disruptions that are part of a modern, connected and global world.